Essays on the U.S. labor market: evidence from immigrants' wages and the downward nominal wage rigidity constraint - McKenzie, Sidonia Lucrisha (Kansas State University, 2024)
This dissertation consists of three essays that focus on the empirical regularities of the U.S. labor market and their consequences for economic opportunities available to native and immigrant workers. In particular, I reexamine two crucial aspects of the U.S. labor market: the disparity in the labor market outcomes of immigrants and the sluggish adjustment of nominal wages over the business cycle. The first essay addresses the question of whether various features of an occupation affect the wages of workers in that occupation. I leverage information on the variation in an occupation's English language skill requirement and the ethnic and nativity concentration in a given occupation and year to explain the native-immigrant wage differences within occupations. I show that the fraction of immigrants in an occupation plays an essential role in explaining this wage gap in the U.S. Furthermore, the nature of this fraction, whether immigrants are co-nationals or from a different birthplace, has a salient effect on the magnitude of the gap. Notably, across state labor markets, a one percent increase in the fraction of immigrant men in the workforce of a given occupation leads to an increase in the wage gap in that occupation by about 20 percentage points on average. On the other hand, if this fraction is from the same birthplace, the within-occupation wage gap narrows substantially by nearly 32 percentage points. In the second essay, I revisit the impact of access to the Supplemental Nutrition Assistance Program (SNAP) on immigrants' labor market outcomes. SNAP stands as one of the largest safety net programs in the United States. Given its significance, the welfare implications of SNAP have been extensively studied from various angles. In particular, applied researchers often focus on the 1996 federal welfare reform, which introduced significant restrictions to SNAP eligibility, creating a clear distinction between citizens (typically the control group) and legal non-citizens (usually the treated group). Subsequent policies that reinstated eligibility for legal non-citizens at different times across states offer a natural setting for a staggered treatment adoption, which is well-suited for a difference-in-differences (DiD) analysis. As previous researchers have done, East (2018) employs this methodology using a two-way fixed effects (TWFE) model to examine the effects of SNAP eligibility. However, recent advancements in empirical estimation, often referred to as the "DiD credibility revolution,'' have highlighted inherent biases in TWFE models, including issues related to "negative weighting'' that can lead to misleading and oppositely signed estimates. These more robust methods cast significant doubt on the validity of the effects reported by earlier studies that employed staggered rollout designs. In this essay, I revisit the effects of SNAP access on immigrants' labor market outcomes, building off the work of East (2018). By employing more recent econometric techniques, I confirm that while SNAP eligibility does indeed reduce immigrants' labor supply—affecting the likelihood of employment—the magnitude of these effects is considerably smaller than previously reported. This finding implies that policy changes impacting SNAP access for vulnerable groups, such as immigrants, should account for the fact that labor supply disincentive effects are relatively modest. The third essay, with Lance Bachmeier and Benjamin Keen, investigates the response of the labor market to substantial increases in oil prices. Our analysis utilizes microdata from the Current Population Survey (CPS) spanning from 1983 to 2018 to construct a linked sample of hourly paid workers who did not change jobs over the interview cycle. The most important finding, which contributes new insights to the literature, is that overtime compensation serves as a crucial margin for firms to adjust to significant increases in oil prices. Specifically, the likelihood of receiving overtime pay declines by nearly 45\% across both blue-collar and white-collar workers due to a reduction in overtime hours. We argue that explanations for the macroeconomic response to oil price shocks may benefit from emphasizing the central role of overtime compensation as a key margin where firms adjust production costs. A second clear takeaway from our analysis is that hours worked fall in most industries in response to large oil price increases. This pattern aligns with the notion that firms are hesitant to reduce wages, opting instead to decrease working hours as a means of cost adjustment.
Keywords: U.S. labor market; DNWR; Immigrants; Wages; SNAP